A crack-bridging model of brick and mortar architecture considering the anisotropic property. (15th May 2023) - Nie, Yunqing; Li, Dongxu; Luo, Qing
Abstract: The attainment of both strength and toughness is a vital requirement for most engineering materials. Unfortunately these properties are generally mutually exclusive. Biological materials, which defeat the conflict of strength versus toughness, provide prototypes to design artificial composites. This paper presents a fracture model of brick and mortar architectures considering the anisotropy of natural materials, to reveal the toughening mechanism of crack-bridging and provide some guidelines for the design of high-performance bioinspired materials. Firstly, we establish an microstructure-based anisotropic fracture model. It is found that to accurately predict the fracture toughness, it is necessary to take into account material anisotropy. Then, the model is used to explore the toughening effect of geometric sizes and material parameters. The results demonstrate that the aspect ratio of brick and the stiffness ratio of brick and mortar are key parameters to influence fracture toughness. In addition, crack-bridging provides a dominant contribution to the crack resistance in the early stage of crack growth, and its contribution is gradually attenuated with crack growth.